Mendesain Putusan Hakim Pengadilan Tata Usaha Negara Tentang Opened Legal Policy: Suatu Upaya Mewujudkan Integritas Peradilan - Alan, Muhammad Fikri; Saputri, Fenolia Intan (Ikatan Hakim Indonesia (IKAHI), 2023)
The Administrative Court Judge's decision according to paragraph 97 section (7) Law Number 5 of 1986 consists of 4 types of decisions, namely: (a) Rejected Decision, (b) Accepted Decision, (c) Not Accepted Decision, (d) Aborted Decision. A State Administrative Decree (KTUN) can be defended, if the KTUN does not actually conflict with the Legislation and AUPB. This raises a new question, can a KTUN be defended on the grounds that the KTUN is an Opened Legal Policy from a State Administrative Agency or Official? In this paper the author tries to formulate an ideal design regarding PTUN decisions under the pretext of opened legal policy. The aim is that in the future there will be no debates regarding all decisions issued by the PTUN which are none other than as a momentum to realize an integrity of the judiciary in the life of the nation and state. The author in his writings uses the normative juridical method with statutory approaches, conceptual approaches, and case approaches.